2012
DOI: 10.1136/heartjnl-2011-300632
|View full text |Cite
|
Sign up to set email alerts
|

Clinical prediction model for death prior to appropriate therapy in primary prevention implantable cardioverter defibrillator patients with ischaemic heart disease: the FADES risk score

Abstract: The risk of death without prior appropriate ICD therapy can be predicted in primary prevention ICD patients with ischaemic heart disease, which facilitates patient-tailored risk estimation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 35 publications
3
26
0
4
Order By: Relevance
“…Thus it could be anticipated that they would have a worse prognosis. This finding is consistent with other studies of ICD patients who have found DM to be an independent risk factor for mortality [25][26][27].…”
Section: Discussionsupporting
confidence: 83%
“…Thus it could be anticipated that they would have a worse prognosis. This finding is consistent with other studies of ICD patients who have found DM to be an independent risk factor for mortality [25][26][27].…”
Section: Discussionsupporting
confidence: 83%
“…The clinical parameters associated with death before appropriate ICD therapy in patients with ischaemic heart disease who had an ICD inserted for primary prevention were assessed in a retrospective cohort study of 900 patients 111. The investigators found that New York Heart Association (NYHA) functional class ≥ III, advanced age, diabetes mellitus, LVEF ≤25%, and a history of smoking were significant independent predictors of death without appropriate ICD therapy, and suggested that this information may facilitate a more patient tailored risk estimation.…”
Section: Ventricular Arrhythmias and Sudden Cardiac Deathmentioning
confidence: 99%
“…Although, according to the large studies mentioned earlier, high mortality risk can be expected to point out patients at low benefit, one could take it to a higher analytical level by trying to identify death prior to ICD discharge as the ideal endpoint for nonbenefit. At our center, we developed a tool to identify patients with ischemic heart disease who, although currently indicated for ICD treatment, will have a high risk of dying prior to actually receiving a potentially life-saving ICD shock [17]. In this study, a total of 900 primary prevention ICD patients with ischemic heart disease were followed up for 669 days (IQR 363-1322 days).…”
Section: Routine Clinical Practice: Identification Of Primary Preventmentioning
confidence: 99%